'On the Measurement of Social Progress and Wellbeing': A Commentary. Issue 3 (18th September 2013) - Marchetti, Raffaele
<x xml:space="preserve">Abstract</x> Prof. Fitoussi and his co‐author Prof. Stiglitz take on the role of norm entrepreneurs, aiming at replacing or at least integrating an old approach to a crucial question – the nature and measurement of well being, with a new one. The end result is not certain. <boxed-text content-type="graphic" id="gpol12070-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>